Goy Israel's multiple others and the birth of the gentile - Ofir, ʿAdi 1951-; Rozen-Tsevi, Yishai 1971- (Oxford Oxford University Press USA - OSO, 2018)
This work traces the development of the term and category of the goy from the Bible to rabbinic literature.
Cover -- Goy: Israel's Multiple Others and the Birth of the Gentile -- Copyright -- Acknowledgments -- Contents -- Introduction -- A Surprising Lacuna -- Strategy and Methodology -- Discourse -- Typology -- Genealogy -- Our Corpus and the Plan of this Book -- 1. Nokhri, Ger, and the Art of Separationin the Hebrew Bible -- Strangers -- The Unrecognized Stranger -- Priestly Strangers, Residents, and Natives -- The Deuteronomic Foreigner -- The Triadic Logic of Separation -- Narratives of Violence and Separation: From the Patriarchs to Sinai -- God and His Others in the Deuteronomistic Works -- The Separation of the Holy in Priestly Sources -- 2. Fragile Particularism, Virtual Universalism -- Ezra-Nehemiah -- Foreign Wives and Alien Priests-the Biopolitics of Separation -- Fragile Identity and Multiple Others -- Separation Performed, Identities Formed -- Prophetic Eschatologies -- 3. The Missing Goy in SecondTemple Literature -- Chauvinism and Plurality -- Flexible Election -- Marriage, Family, Tribe, and Nation -- The Dialectic of Openness and Seclusion -- Enemies and Other Nations -- 4. Nations and Goyim, Hellēnes and Others -- Individuation and Generalization -- Between Ethnos and Politeia:Philo and Josephus -- Philo -- Josephus -- Diasporism -- The Temple Inscription -- 5. Paul and the Non-Ethnic Ethnē -- The Proliferation of Ethnē -- Why does paul need the individualized,generic gentile? -- Political Theology -- The Disappearance of Gentiles in Earlychristianity -- 6. The Formation of the Binary Structurein Early Rabbinic Literature -- The Erasure of the in-Betweens -- Gerim -- Samaritans -- Apostates (meshumadim) and Heretics (minim) -- Noahides and God-Fearers -- Generating a Polarized World -- The Limits of Rabbinic Eschatology -- Toward a New Paradigm -- 7. One Goy, Multiple Language Games -- Goyim in Halakhic Discourse.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books